Chloride concentrations and calculated gas hydrate saturations in sediments collected at Four-Way Closure Ridge, RV Sonne cruise SO266/1, South China Sea - Lin, Saulwood; Bohrmann, Gerhard (PANGAEA, 2022)
During cruise SO266/1 deep sediment cores were collected using MARUM-MeBo200 from Formosa Ridge and Four-Way Closure Ridge, South China Sea. Near-surface sediments were retrieved from same positions by use of a gravity corer. Pore water was sampled from selected core depths. Concentrations of pore water chloride concentrations were determined by ion chromatography. Gas hydrate saturation of the pore space were calculated using empirical equations based on pore water chloride concentration anomalies. Data pairs indicated are from single measurements for pore water samples from individual cores.